Natural killer cells and hepatitis C: action and reaction. Issue 2 (28th September 2010) - Cheent, Kuldeep; Khakoo, Salim I
Abstract : In 1989, hepatitis C virus (HCV) was first identified as the infectious agent responsible for human non-A, non-B hepatitis.1 Two decades later, HCV remains a global public health problem with a suboptimal response rate to treatment and the absence of a protective vaccine. Recent work has highlighted the influence of the innate immune system, and in particular natural killer cells, on the outcome and pathology of HCV infection. These cells are considerably more complex than was originally thought and their role in viral infections is currently being unravelled. This review summarises our emerging understanding of natural killer cells in HCV infection.